2020
DOI: 10.3897/jhr.77.52904
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the meconia of European egg parasitoids of Halyomorpha halys

Abstract: Halyomorpha halys is a severe invasive Asian pest worldwide and classical biological control is foreseen as the most promising control method. Egg parasitoids appear to be the most important natural enemies of this pest, especially the Asian hymenopteran Trissolcus japonicus. In the invaded areas, only a few egg parasitoid species have been able to adopt H. halys as a host. Anastatus bifasciatus is the most common native egg parasitoid of H. halys in Europe, but reaches only low levels of parasitization, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…sinicus , the expansion of which could cause possible problems in the future, limiting the impact of H. halys natural enemies. Acroclisoides sinicus was recently detected in many countries worldwide, but it is suspected to be an Asian species and its influence on the host–parasitoid trophic chain should be further investigated [ 28 , 42 ]. The generalist parasitoid An.…”
Section: Discussionmentioning
confidence: 99%
“…sinicus , the expansion of which could cause possible problems in the future, limiting the impact of H. halys natural enemies. Acroclisoides sinicus was recently detected in many countries worldwide, but it is suspected to be an Asian species and its influence on the host–parasitoid trophic chain should be further investigated [ 28 , 42 ]. The generalist parasitoid An.…”
Section: Discussionmentioning
confidence: 99%
“…This was also demonstrated by the co-presence of the meconium of the primary parasitoid and the hyperparasitoid within the H. halys egg; thus, the pentatomid egg shell provides a protected environment for developing A. sincus immatures, which feed on sceliond pupae. In all cases so far observed, the meconium of A. sinicus is deposited directly on the meconium of its host and not randomly within the pentatomid egg [ 23 ]. The olfactory cues in the meconium could assist female A. sinicus in their search for hosts and subsequent acceptance, as is known to be the case with many parasitoid and predator species [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pupal stage occurs approximately from 7 to 9 days, at which time the pharate adult is recognizable (see the results, Table 2 and Table 3 ). Our preliminary studies revealed that at around day 5 following primary parasitization, the meconium is expelled and is often visible through the cuticle of the host egg (in T. mitsukurii , an additional black ring appears below the operculum of the host egg) [ 8 , 23 ]. When this occurs, the immature parasitoid enters, transitionally, the pupal stage.…”
Section: Methodsmentioning
confidence: 99%
“…If the cause of mortality could not be diagnosed, eggs were counted as unhatched. When parasitoids had already emerged in the field, to determine the parasitoid previously contained, shapes of exit holes and meconia were examined and compared to the descriptions of Sabbatini-Peverieri et al [48,49].…”
Section: Field Survey Of Native and Non-native Parasitoids Of Halyomorpha Halysmentioning
confidence: 99%